The consequences of early childhood growth failure over the life course - Hoddinott, John F.; Maluccio, John A.; Behrman, Jere R.; Martorell, Reynaldo; Melgar, Paul; Quisumbing, Agnes R.; Ramirez-Zea, Manuel; Stein, Aryeh D.; Yount, Kathryn M. (International Food Policy Research Institute, 2011)
This paper examines the impact over the life course of early childhood growth failure as measured by achieved height at 36 months. It uses data collected on individuals who participated in a nutritional supplementation trial between 1969 and 1977 in rural Guatemala and who were subsequently reinterviewed between 2002 and 2004. It finds that individuals who did not suffer growth failure in the first three years of life complete more schooling, score higher on tests of cognitive skill in adulthood, have better outcomes in the marriage market, earn higher wages and are more likely to be employed in higher-paying skilled labor and white-collar jobs, are less likely to live in poor households, and, for women, fewer pregnancies and smaller risk of miscarriages and stillbirths. Growth failure has adverse impacts on body size and several dimensions of physical fitness in adulthood but does not have marked effects on risk indicators of cardiovascular and related chronic diseases. These results provide a powerful rationale for investments that reduce early-life growth failure.